Termografia infravermelha para verificação do efeito da gordura corporal na temperatura cutânea - Salamunes, Ana Carla Chierighini (2017)
The increase in the prevalence of overweight and obesity indicate the need of precise methods to estimate body composition. The aim of this study was to analyze the possibility of calculating body fat percentage of young women, aged 18 to 35 years, using infrared thermography (IRT), which estimates a body's surface temperature by means of its infrared radiation. Sample was 130 women aged 26,06 ± 4,41 years and with body mass index (BMI) from 18,5 to 24,99kg/m², from the city of Curitiba. Participants were evaluated with three methods: anthropometry, by means of stature, body mass, BMI and body circumferences from arm, forearm, waist, abdomen (umbilicus and largest portion), hip, thigh and leg; body composition, by lean mass per anatomical segment, body fat percentage (BF%) and percentage of fat per anatomical site (F%) with Dual-Energy X-Ray Absorptiometry; and skin surface temperature (T), with IRT, in 30 regions of interest (ROI) on the trunk, upper and lower limbs from anterior and posterior views. Mean, minimum and maximum temperatures (TMe, TMi, TMa) were registered from each ROI. Sample was divided in groups of high and low F% of trunk, upper and lower limbs from right and left sides separately. Student's T test was used to compare lean mass and TMe of these groups. For all women as a single group, Pearson's correlation was calculated for anthropometric variables and T with BF%. In this analysis, TMe, TMi and TMa were considered as the mean values between left and right sides of the same ROI. Variables with the most significant results were used to estimate mathematical models for the calculus of BF%. Three equations were developed based on IRT and body circumferences and one without IRT. Groups with the highest F% had lower TMe results in the ROI of the respective segment. Lean mass was significantly different only between groups of high and low F% on the left upper limb. All body circumferences correlated positively with BF%. Palm variables of T were the only ones positively correlated with BF%. Most T values from other ROI were negatively correlated with BF%. The most significant mathematical model with IRT was calculated with TMe from posterior lower limbs, TMi from posterior arms, TMa from palms and the circumference of the largest portion of the abdomen (R = 0,764 and R² = 0,583). The equation based on body circumferences was estimated with the circumference of the largest portion of the abdomen, hip circumference and body mass (R = 0,744 e R² = 0,554). It has been concluded that skin surface temperature is influenced by body fat. The IRT may be an effective instrument to estimate BF%.